2018
DOI: 10.3389/fneur.2018.00097
|View full text |Cite
|
Sign up to set email alerts
|

Heparin: The Silver Bullet of Aneurysmal Subarachnoid Hemorrhage?

Abstract: Various neurological diseases have recently been associated with neuroinflammation and worsening outcomes. Subarachnoid hemorrhage has been shown to generate a potent neuroinflammatory response. Heparin is a potential effective anti-inflammatory agent to prevent initial injury as well as delayed neurological decline. Different mechanisms of action for heparin have been proposed including, but not limited to the binding and neutralization of oxyhemoglobin, decreased transcription and signal transduction of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Heparin and low molecular weight heparin infusions have been evaluated in aSAH with inconsistent results . Heparin has antiinflammatory properties different than its role in anticoagulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparin and low molecular weight heparin infusions have been evaluated in aSAH with inconsistent results . Heparin has antiinflammatory properties different than its role in anticoagulation.…”
Section: Resultsmentioning
confidence: 99%
“…Heparin and low molecular weight heparin infusions have been evaluated in aSAH with inconsistent results. [101][102][103] Heparin has antiinflammatory properties different than its role in anticoagulation. It is thought to attenuate the inflammatory response and restore bloodbrain barrier integrity.…”
Section: Heparin and Low Molecular Weight Heparinmentioning
confidence: 99%
“…However, its effect on cerebral edema in patients with aSAH has not been studied. 12 One mediator of microvascular constriction is endothelin-1 (ET-1). Heparin also can decrease the transcription of ET-1 and ET-1 promoters.…”
Section: Discussionmentioning
confidence: 99%
“…flammation, which are all the relevant mechanisms for the treatment of aSAH-induced brain injury. 11,12 Preclinical investigations in rodent models found that heparin reduced edema, neuroinflammation, demyelination, and transsynaptic neuronal apoptosis. 13 Because of the promising potential of heparin, we aimed to evaluate the latest evidence on the safety and efficacy of its usage in treating aSAH.…”
mentioning
confidence: 99%
“…Several studies have indicated the beneficial role of heparin. By using low dose heparin and its nanoparticles, it was observed that cognitive outcomes were better and the occurrence of vasospasm was reduced and cerebral ischemia was deferred for a brief period [66]. Nevertheless, advanced studies have proved that heparin has a diminutive effect on vasospastic damage, especially SAH-associated whereas it may still be effective in lowering inflammatory-related injuries that are related to SAH [67].…”
Section: Discussionmentioning
confidence: 99%